Atividades de enriquecimento curricular no 1º ciclo do ensino básico - Machado, Joaquim (2014)
We contextualize the CURRICULUM ENRICHMENT ACTIVITIES - (AEC - Atividades de Enriquecimento Curricular) in their social dimension, in the process of institutionalization of school education and redefinition of their goals and functions. In particular, we focus on politics of adjustment of the school schedules to the needs of the families. Our survey was conducted in a region by the coastline of the North of Portugal. It aims to identify the models of organization of the AEC and be aware of the structural changes in the primary school. It is a qualitative study based on interactional observation, analysis of documents done at the schools as well as informal discussions with the teachers of the class and the ones of the AEC to identify their opinion and ideas about the introduced changes. We focus on the perceptions of teachers of the changes - regarding organizational, curricular and pedagogic aspects, as well as the advantages and challenges of the action of the municipal government as the promoter of the AEC.